High‐intensity focused ultrasound (HIFU) for definitive treatment of prostate cancer - Cordeiro, Ernesto R.; Cathelineau, Xavier; Thüroff, Stefan; Marberger, Michael; Crouzet, Sebastien; de la Rosette, Jean J.M.C.H. (BJU international, 2012)
What's known on the subject? and What does the study add? Novel therapeutic methods have emerged in recent years as ‘focal’ treatment alternatives in which cancer foci can be eradicated and greatly reducing the associated side‐effects of radical treatment. High‐intensity focused ultrasound (HIFU) seems to result in a well fitted technology, which has proven short‐ to medium‐term cancer control, with a low rate of complications comparable with those of established therapies. This is an up‐to‐date review of the available literature on HIFU as a definitive treatment of prostate cancer. It describes the technique in a comprehensive approach in terms of technical features, procedure, indications, and gives an overview of its historical background; finally, we present the future applications of HIFU and its development trend. OBJECTIVES • To provide an up‐to‐date review of the available literature on high‐intensity focused ultrasound (HIFU) as a definitive treatment of prostate cancer. • To present the technique in a comprehensive approach, comparing the available devices according to the existing evidence in terms of technical features, procedure, indications, and to give an overview of its historical background; and finally, to discuss future applications of HIFU and its development trend. MATERIALS AND METHODS • A systematic literature search was conducted using MEDLINE and EMBASE via Ovid databases (January 2000 to December 2011), to identify studies on HIFU for treatment of prostate cancer. • Only English‐language and human‐based full manuscripts that reported on case series studies with >50 participants, patient characteristics, efficacy and safety data were included. RESULTS • No randomised controlled trials were identified by the literature search. We identified 31 uncontrolled studies that examined the efficacy of HIFU as primary treatment and two studies that examined the efficacy of HIFU as salvage treatment. • Most treated patients had localised prostate cancer (stage T1–T2); Gleason scores of 2–10 and mean prostate specific antigen (PSA) values of 4.6–12.7 ng/mL. The mean age range of the patients was 64.1–72 years. The mean follow‐up ranged from 6.4 to 76.8 months. Negative biopsy rates ranged from 35 to 95%. PSA nadirs ranged from 0.04 to 1.8 ng/mL. The 5‐year disease‐free survival rates ranged from 61.2 to 95%; 7‐ and 8‐year disease free survival rates ranged from 69 to 84%. • The most common complications associated with the HIFU procedure as the primary treatment included: urinary retention (<1–20%); urinary tract infections (1.8–47.9%); stress or urinary incontinence (<1–34.3%); and erectile dysfunction (20–81.6%). • Recto‐urethral fistula was reported in <2% of patients. • Treatment‐related morbidity appeared to be reduced by the combination of transurethral resection (TURP) of the prostate and HIFU. CONCLUSIONS • Novel therapeutic methods have emerged in recent years as ‘focal’ treatment alternatives, in which cancer foci could be eradicated by greatly reducing the associated side‐effects of radical treatment. • HIFU seems to result in short‐ to medium‐term cancer control, with a low rate of complications comparable with those of established therapies. • However, longer‐term follow‐up studies are needed to evaluate cancer‐specific and overall survival. If available promising results on HIFU for definitive treatment of prostate cancer are confirmed in future prospective trials, focal therapy could start to challenge the current standard of care.